2013
DOI: 10.1017/s0305004113000297
|View full text |Cite
|
Sign up to set email alerts
|

Invariants of topological relative right equivalences

Abstract: Let (V, 0) be the germ of an analytic variety in C n and f an analytic function germ defined on V. For functions with isolated singularity on V, Bruce and Roberts introduced a generalization of the Milnor number of f, which we call Bruce-Roberts number, μ B R (V, f ). Like the Milnor number of f, this number shows some properties of f and V. In this paper we investigate algebraic and geometric characterizations of the constancy of the Bruce-Roberts number for families of functions with isolated singularities o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In [1], it is shown that if (X, 0) is a weighted homogeneous hypersurface with an isolated singularity and if f and g are C 0 -R X -equivalent function germs then μ BR (f, X) = μ BR (g, X). The following example shows that the converse of this result is not true.…”
Section: Weighted Homogeneous Functions and Varietiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In [1], it is shown that if (X, 0) is a weighted homogeneous hypersurface with an isolated singularity and if f and g are C 0 -R X -equivalent function germs then μ BR (f, X) = μ BR (g, X). The following example shows that the converse of this result is not true.…”
Section: Weighted Homogeneous Functions and Varietiesmentioning
confidence: 99%
“…THEOREM 3.6. Let (X, 0) ⊂ ‫ރ(‬ n , 0) be a weighted homogeneous hypersurface with isolated singularity, let f : ‫ރ(‬ n , 0) → ‫ރ‬ be a weighted homogeneous R X -finitely determined function and let f t be a deformation of f as in (1). The following statements are equivalent:…”
Section: Weighted Homogeneous Functions and Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…. , μ (1) (f ), μ (0) (f )), where μ (i) (f ) denotes the Milnor number of the restriction of f to a generic linear subspace of dimension i of C n , for i = 1, . .…”
Section: Introductionmentioning
confidence: 99%